2014
DOI: 10.1016/j.eneco.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Oil price uncertainty and manufacturing production

Abstract: Given the rapid rise and volatility of oil prices, the paper investigates the e¤ect of oil price uncertainty on the South African manufacturing production using monthly observations covering the period 1974:02 to 2012:12. In addition, we quantify the responses of manufacturing production to positive and negative oil price shocks. We examine the dynamic relationship using a bivariate GARCH-in-mean VAR simultaneously estimated with a full information maximum likelihood technique. The conditional standard deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…While this is likely to be a more serious concern for developing countries with lesser ability to engage in efficient monetary and fiscal policies and other means of preventing adverse effects on the structure of industry, Dissou (2010) has shown that it also is a common result in developed countries like Canada. Aye et al (2014), among many others, have shown that adverse effects on tradable goods can occur even if the country is an exporter, not of oil, but rather of minerals and other primary products which could have similar effects on the real exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While this is likely to be a more serious concern for developing countries with lesser ability to engage in efficient monetary and fiscal policies and other means of preventing adverse effects on the structure of industry, Dissou (2010) has shown that it also is a common result in developed countries like Canada. Aye et al (2014), among many others, have shown that adverse effects on tradable goods can occur even if the country is an exporter, not of oil, but rather of minerals and other primary products which could have similar effects on the real exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nkomo, , ; Swanepoel, ; Chisadza et al ., ; Gupta and Modise, ; Aye et al . among others). However, none of these studies analysed the effect of oil price volatility except Aye et al .…”
Section: Introductionmentioning
confidence: 88%
“…Aye et al . () examined the volatility of oil prices and its effects on the manufacturing sector in South Africa. This is the first paper to account for in particular the volatility of oil prices in South Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also supported by Hooker [29], who argued that oil price changes significantly caused US inflation and productivity, and Hamilton [30], who analyzed the impact of oil price changes on US macroeconomic components during 2007 to 2008. In particular, Aye et al [31] analyzed the effect of oil price changes on manufacturing production in South Africa. The analysis results suggested that oil price changes significantly and negatively impact South Africa's manufacturing production and that manufacturing production responded asymmetrically to increasing and decreasing oil price changes.…”
Section: Determinant Of Environmental Productivitymentioning
confidence: 99%